Examining Lebanon's Resilience Through a Water-Energy-Food Nexus Lens - Daher, Bassel; Hamie, Silva; Pappas, Konstantinos; Roth, Julie (Frontiers in Sustainable Food Systems, 2022)
Lebanon faces a mix of underlying political and economic challenges, shocks, and triggering events that threaten the sustainability and resilience of its interconnected resource systems. The complex nature of these pressures begs for a systems approach to better understand the existing interconnections and to support the co-creation of cross-sectoral solutions to address them. This article specifically aims to: 1) conduct a scoping review of the existing literature and current events to identify interconnections between water-, energy-, and food-related challenges as they relate to the underlying conditions and triggering events at play in the context of Lebanon; 2) highlight ways in which the Water-Energy-Food (WEF) Nexus is a useful lens through which to understand and act upon issues at different scales; and 3) identify emergent themes including decentralization and systems thinking and their roles as catalysts toward more resilient resource systems. The examination concludes with two main recommendations: first, to create platforms and opportunities for interactive resource planning and decision making to facilitate systems-thinking for top-down WEF management; and second, to empower decentralized initiatives at the local level to build resilient, bottom-up solutions to WEF challenges.